1995
DOI: 10.1111/j.1365-2141.1995.tb05246.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of glucose‐6‐phosphate dehydrogenase (G6PD) deficiency in Spain: identification of two new point mutations in the G6PD gene

Abstract: In order to explore the nature of glucose-6-phosphate dehydrogenase (G6PD) deficiency in Spain, we have analysed the G6PD gene in 11 unrelated Spanish G6PD-deficient males and their relatives by using the polymerase chain reaction and single-strand conformation polymorphism (PCR-SSCP) analysis combined with a direct PCR-sequencing procedure and PCR-restriction enzyme (RE) analysis. We have identified eight different missense mutations, six of which have been reported in previously described G6PD variants. In n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Our study clearly demonstrates that the mutation 188 Ser →Phe (G6PD Mediterranean) is strongly associated with haemolytic events whereas the mutation 282 Asp →Hys (Seattle) is always associated with a non-haemolytic phenotype (Table I). This is in agreement with a study of nine unrelated Spanish subjects with favism, none of whom was found to bear the G6PD Seattle variant, suggesting that this variant, which is polymorphic in Spain, is asymptomatic (Rovira et al, 1995). As for other variants, the small number of cases does not allow us to draw meaningful conclusions regarding the haemolytic phenotype.…”
Section: Discussionsupporting
confidence: 85%
“…Our study clearly demonstrates that the mutation 188 Ser →Phe (G6PD Mediterranean) is strongly associated with haemolytic events whereas the mutation 282 Asp →Hys (Seattle) is always associated with a non-haemolytic phenotype (Table I). This is in agreement with a study of nine unrelated Spanish subjects with favism, none of whom was found to bear the G6PD Seattle variant, suggesting that this variant, which is polymorphic in Spain, is asymptomatic (Rovira et al, 1995). As for other variants, the small number of cases does not allow us to draw meaningful conclusions regarding the haemolytic phenotype.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, by the use of molecular analysis, the G6PD Seattle mutation was found in Spain (28), in the Canary Islands (29,30) and in the north African Berber (30). Nafa et al (13) found the Seattle mutation associated with haplotype (Ϫ Ϫ ϩ ϩ Ϫ Ϫ) in Algeria and, and Medina et al found in England an association to the same haplotype although restricted to four RFLPs (PvuII, PstI, BclI, and NlaIII) (31).…”
Section: Tablementioning
confidence: 99%
“…Among these, G6PD Mediterranean (563 C-+T), G6PD A-(376 A+G with either 202 G+A or 968 T-C), G6PD Seattle (844 G+C), G6PD Aures (143 T-C), and G6PD Union (1360 C+T), have been found in Spain (Rovira et al, 1994(Rovira et al, , 1995. Here, the G6PD gene has been characterized in five unrelated Spanish G6PD deficient males who had presented clinically with favism.…”
Section: Mutation Analysismentioning
confidence: 90%
“…The DNA region from the G6PD gene encompassing each point mutation was selectively amplified by PCR as described previously (Poggi et al, 1990;Rovira et al, 1995). Naturally occurring restriction sites enabled us to distinguish the normal from mutant genes as follows: Fok I for the 376 A+G mutation of G6PD A and G6PD A-; Nla 111 for the 202 G-+A mutation of the most common form of G6PD A-; Bst NI for the 680 G+T mutation and Nci I for the 968 T+C mutation of the two additional G6PD A-genotypes; Mbo I1 for the 563 C+T mutation of G6PD Mediterranean; and Hha I for the 1360 C+T mutation of G6PD Union.…”
Section: Pcr-restriction Fragment Analysismentioning
confidence: 99%